Bystander alertness, responsiveness, and barriers to providing first aid for sudden cardiac arrest in Indonesia: A preliminary community-based study - Yohanes K. Windi; Loetfia D. Rahariyani; Nikmatul Fadilah; Eko R. Wiyatno (Narra Sains Indonesia, 2026)
Bystanders can play a critical role in improving survival after sudden cardiac arrest (SCA), yet hesitation and inaction remain common. The aim of this study was to assess bystander alertness, responsiveness, and barriers to providing first aid for SCA in an Indonesian community setting. A cross-sectional survey was conducted among 500 residents attending four Community Health Centers in Sidoarjo District, East Java, Indonesia. A structured, self-administered questionnaire assessed recognition of heart disease, perceptions of life-threatening cardiac conditions, intended responses to SCA, types of medical aid sought, reasons for not providing first aid, and specific first-aid actions. Data were analyzed using descriptive statistics and Chi-squared tests. Overall, respondents showed limited recognition of SCA as a distinct cardiac emergency and were more familiar with heart attack and coronary disease. Although SCA is highly time-critical, it was not commonly perceived as the most life-threatening heart condition. Most respondents preferred to seek medical help rather than provide immediate first aid, while direct bystander intervention was uncommon. Among those who would not intervene, fear of being blamed, lack of knowledge, and perceived incompetence were the main barriers. Among respondents willing to help, intended actions were more commonly directed toward waking the victim or using culturally familiar practices, whereas cardiopulmonary resuscitation (CPR) was rarely reported. Significant differences were observed across all assessed response domains (p<0.001). These findings indicate low community alertness and responsiveness to SCA in this Indonesian setting. Community-based SCA education, hands-only CPR training, clearer emergency response guidance, and culturally sensitive public messaging are needed to improve bystander readiness and reduce delays in first aid.